Intrauterine Infection and Spontaneous Midgestation Abortion: Is the Spectrum of Microorganisms Similar to That in Preterm Labor? - Helen M. McDonald; Helen M. Chambers (Hindawi Limited, 2000)
Objective: To determine whether microorganisms associated with intrauterine infection and preterm labor play a contributing role in midgestation abortion.